1995
DOI: 10.1128/aem.61.9.3202-3207.1995
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal floras of populations that have a high risk of colon cancer

Abstract: The fecal floras of polyp patients, Japanese-Hawaiians, North American Caucasians, rural native Japanese, and rural native Africans were compared. The polyp patients and Japanese-Hawaiians were considered to be groups at high risk of colon cancer, and the rural native Japanese and rural native Africans were considered to be groups at low risk. The North American Caucasians were found to have a flora composition intermediate between these two groups. Fifteen bacterial taxa from the human fecal flora were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
189
1
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(199 citation statements)
references
References 15 publications
6
189
1
3
Order By: Relevance
“…1 Colonization of the gastrointestinal tract starts immediately after birth 11 and is of great importance for the composition of the permanent flora in adults. 23 Furthermore, the intestinal microflora affects the gut-associated lymphoid tissue, and their interaction appears to be essential for development of appropriate regulatory circuits of the immune response. 11 Environmental factors influencing the intestinal microflora include infections, diet, and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…1 Colonization of the gastrointestinal tract starts immediately after birth 11 and is of great importance for the composition of the permanent flora in adults. 23 Furthermore, the intestinal microflora affects the gut-associated lymphoid tissue, and their interaction appears to be essential for development of appropriate regulatory circuits of the immune response. 11 Environmental factors influencing the intestinal microflora include infections, diet, and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies showed that members of the phylum Cyanobacteria (one phylotype) can be found in the human gastrointestinal samples (Eckburg et al, 2005), even though isolates from this group have not been reported. Furthermore, six phylotypes of the subphylum of a-Proteobacteria were detected by SSU rRNA gene sequencing, while there is only one known a-proteobacterial gastrointestinal isolate -Gemmiger formicilis (Holdeman et al, 1976;Benno et al, 1986;Moore and Moore, 1995;Macfarlane et al, 2004). Unfortunately, no 16S rRNA gene sequence is available for this species.…”
Section: Cultured Versus Unculturedmentioning
confidence: 99%
“…Extensive past surveys of the cultivable human intestinal micro£ora [25,26] showed that the colon harbours signi¢cant populations of genera, such as Clostridium, Eubacterium and Fusobacterium that include butyrate-producing species. The relationships of these bacteria are, however, currently undergoing rapid revision in the light of information from 16S rRNA sequencing (e.g.…”
Section: Butyrate-producing Bacteria^diversity Phylogeny and Culturamentioning
confidence: 99%